Β sialon phosphor and light-emitting device

By coating the surface of the β-sialon phosphor, the reflection and scattering of light are reduced, and the absorption rate of light is improved, and the problem that β-sialon phosphor in the prior art is difficult to achieve high brightness and high light flow, achieving efficient light emission effects.

JP2025050543APending Publication Date: 2025-04-04NICHIA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023159394
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing β-sialon phosphors and light emitting devices are difficult to achieve light emission of high brightness and high light flow.

Method used

A β-sialon phosphor with a surface coating is used, the refractive index of the surface layer is less than that of the phosphor particles, and the mass of the surface layer is at least 0.4% when the total mass is 100%.

Benefits of technology

By reducing the reflection and scattering of light, the absorption of light is improved, so that the β-sialon phosphor can efficiently convert the absorbed light into light of high brightness and high light flow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025050543000001_ABST
    Figure 2025050543000001_ABST
Patent Text Reader

Abstract

To provide a β sialon phosphor and a light-emitting device.SOLUTION: A β sialon phosphor includes phosphor particles having a composition represented by the formula (I), and a coating layer arranged on surfaces of the phosphor particles and having a refractive index smaller than that of the phosphor particles, wherein when the β sialon phosphor is measured by inductively coupled plasma-atomic emission spectroscopy, an amount of the coating layer is 0.4 mass% or more based on 100 mass% of a total amount of the phosphor particles and the coating layer. Si6-zAlzOzN8-z:Euy (I), (in the formula (I), y and z satisfy 0<y≤1.0 and 0<z≤4.2).SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a β-sialon phosphor and a light emitting device. [Background technology]

[0002] A light-emitting device including a light-emitting diode (LED) and a phosphor is known. The phosphor absorbs the excitation light emitted from the LED and emits light having an emission peak wavelength in a specific wavelength range. As a phosphor, a β-sialon phosphor is known that absorbs the excitation light emitted from the LED and has an emission peak wavelength in the visible light region.

[0003] Patent Document 1 discloses a phosphor having a base material of β-sialon, Eu as a solid solution as a luminescent center, and a 10% diameter of 7 to 20 μm and a 90% diameter of 50 to 90 μm as measured by a laser diffraction particle size distribution measurement method. Patent Document 2 discloses a method for producing a β-sialon phosphor, in which a firing step is performed at least twice, and in the first firing step, a phosphor raw material for the first firing is prepared in which the concentration of the activator element is reduced below the desired concentration, and this is fired. The activator element is further added to the obtained first-fired raw material, and the resulting phosphor raw material for the second firing is fired. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-326981 A [Patent Document 2] JP 2013-173868 A Summary of the Invention [Problem to be solved by the invention]

[0005] It is desirable for phosphors to have high brightness, and it is desirable for light emitting devices that include phosphors to emit light with a high luminous flux. The present disclosure aims to provide a β-sialon phosphor that has high absorption of excitation light and emits high-brightness light, and a light-emitting device that includes the β-sialon phosphor and emits light with a high luminous flux.

Means for Solving the Problems

[0006] A first aspect is a β-sialon phosphor including phosphor particles having a composition represented by the following formula (I), and a coating layer disposed on the surface of the phosphor particles and having a refractive index smaller than that of the phosphor particles. When the β-sialon phosphor is measured by inductively coupled plasma optical emission spectrometry and the total of the phosphor particles and the coating layer is 100% by mass, the coating layer is 0.4% by mass or more. Si 6-z Al z O z N 8-z :Eu y (I) (In formula (I), y and z satisfy 0 < y ≤ 1.0 and 0 < z ≤ 4.2.)

[0007] A second aspect is a light-emitting device including a wavelength conversion member including the β-sialon phosphor and a light-transmitting material, and a light-emitting element having an emission peak wavelength in the range of 380 nm or more and 500 nm or less.

Effects of the Invention

[0008] According to the present disclosure, it is possible to provide a β-sialon phosphor that has high absorption of excitation light and emits high-brightness light, and a light-emitting device that includes the β-sialon phosphor and emits light with a high luminous flux.

Brief Description of the Drawings

[0009] [Figure 1] It is a schematic cross-sectional view showing an example of a light-emitting device. [Diagram 2] It is a flowchart showing an example of a method for manufacturing a β-sialon phosphor. [Diagram 3] It is a flowchart showing an example of a method for manufacturing a β-sialon phosphor. [Figure 4]1 is a flowchart showing an example of a method for producing a β-sialon phosphor. [Diagram 5] 1 is a SEM photograph of a backscattered electron image at a magnification of 10,000 times in a cross section of the β-sialon phosphor according to Example 3. [Figure 6A] FIG. 4 is a partially enlarged view of a SEM photograph of a backscattered electron image at a magnification of 30,000 times in a cross section of the β-sialon phosphor according to Example 3. [Figure 6B] FIG. 4 is a partially enlarged view of a SEM photograph of a backscattered electron image at a magnification of 30,000 times in a cross section of the β-sialon phosphor according to Example 3. [Figure 7A] 2 is a SEM photograph of a secondary electron image at a magnification of 5000 times of the β-sialon phosphor according to Example 1. [Figure 7B] 2 is a SEM photograph of a secondary electron image at a magnification of 100,000 times of the β-sialon phosphor according to Example 1. [Figure 8A] 2 is a SEM photograph of a secondary electron image at a magnification of 5000 times of the β-sialon phosphor according to Comparative Example 1. [Figure 8B] 2 is a SEM photograph of a secondary electron image at a magnification of 100,000 times of the β-sialon phosphor according to Comparative Example 1. [Figure 9A] 1 is a SEM photograph of a secondary electron image at a magnification of 5000 times of the β-sialon phosphor according to Comparative Example 2. [Figure 9B] 1 is a SEM photograph of a secondary electron image at a magnification of 100,000 times of the β-sialon phosphor according to Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The β-sialon phosphor and light emitting device according to the present disclosure will be described below. However, the following embodiments are merely examples for embodying the technical ideas of the present disclosure, and the present disclosure is not limited to the following β-sialon phosphor and light emitting device. The relationship between the color name and the chromaticity coordinates, and the relationship between the wavelength range of light and the color name of monochromatic light are in accordance with JIS Z8110.

[0011] The β-sialon phosphor includes phosphor particles having a composition represented by the following formula (I) and a coating layer disposed on the surface of the phosphor particles and having a refractive index smaller than that of the phosphor particles. When the β-sialon phosphor is measured by inductively coupled plasma-atomic emission spectrometry (ICP-AES) and the total of the phosphor particles and the coating layer is 100% by mass, the coating layer is 0.4% by mass or more. Si 6―z Al z O z N 8-z :Eu y (I) (In formula (I), y and z satisfy 0 < y ≤ 1.0 and 0 < z ≤ 4.2.)

[0012] Since the β-sialon phosphor includes a coating layer having a refractive index smaller than that of the phosphor particles on the surface of the phosphor particles having the composition represented by the formula (I), the absorption of light from the excitation light source by the phosphor particles is increased, and the light absorbed by the phosphor particles can be wavelength-converted to emit high-brightness light. The refractive index of the phosphor particles having the composition represented by the formula (I) is silicon nitride Si 3 N 4The refractive index of light having a wavelength of 589.3 nm (D line of sodium), which is generally expressed as the refractive index of optical materials, is approximately 2.06. The refractive index of the coating layer varies depending on the raw material constituting the coating layer or the elements contained in the raw material constituting the coating layer. The coating layer may be made of an inorganic material or an organic material. When the coating layer is made of an inorganic material, the inorganic material may be a nitride, a halide, or an oxide. The coating layer is preferably an oxide layer made of an oxide. When the coating layer is made of an organic material, for example, a polymer compound may be used. When the coating layer is an oxide layer made of an oxide, the refractive index varies depending on the elements contained in the coating layer. For example, when the coating layer is an oxide layer made of an oxide containing silicon, and the oxide contains silicon dioxide, the refractive index of the coating layer when irradiated with light having a wavelength in the range of 380 nm to 780 nm is within the range of approximately 1.45 to approximately 1.50, which is smaller than the refractive index of the phosphor particles. When a coating layer having a refractive index smaller than that of the phosphor particles is disposed on the surface of the phosphor particles, the coating layer reduces the reflection and scattering of light on the surface of the phosphor particles, making it easier for light to pass through and increasing the light absorptance of the phosphor particles. When the light absorptance of the phosphor particles is increased, the phosphor particles can convert the wavelength of the light absorbed with high absorptance, and emit light with high brightness.

[0013] When the β-sialon phosphor is included in the wavelength conversion member of the light emitting device, it is preferable that the wavelength conversion member includes a light-transmitting material and a β-sialon phosphor, and the absolute difference between the refractive index of the light-transmitting material and the refractive index of the coating layer of the β-sialon phosphor is within a range of 0.01 to 0.80. When the absolute difference between the refractive index of the light-transmitting material included in the wavelength conversion member and the refractive index of the coating layer of the β-sialon phosphor is within a range of 0.01 to 0.80, the difference between the refractive index of the light-transmitting material of the wavelength conversion member and the refractive index of the coating layer of the β-sialon phosphor becomes small, and the light-transmitting material and the coating layer reduce light reflection and scattering, making it easier for light to transmit, and increasing the light absorptance of the phosphor particles. In addition, when the difference between the refractive index of the light-transmitting material included in the wavelength conversion member and the refractive index of the coating layer of the β-sialon phosphor is within the range of 0.01 to 0.80 in absolute value, even when the light absorbed by the phosphor particles is wavelength-converted and emitted to the outside of the light-emitting device, the wavelength-converted light is more likely to pass through the coating layer and the light-transmitting material, and a high luminous flux of light can be emitted from the light-emitting device. The difference between the refractive index of the light-transmitting material included in the wavelength conversion member and the refractive index of the coating layer of the β-sialon phosphor may be within the range of 0.01 to 0.70 in absolute value, 0.01 to 0.60, 0.01 to 0.50, 0.02 to 0.30, 0.02 to 0.20, or 0.03 to 0.12. It is more preferable that the refractive index of the light-transmitting material of the wavelength conversion member is smaller than the refractive index of the coating layer of the β-sialon phosphor. When the refractive index of the light-transmitting material contained in the wavelength conversion member is smaller than the refractive index of the coating layer of the β-sialon phosphor, the refractive index gradually decreases in the order of the phosphor particles, the coating layer, and the light-transmitting material, and the light-transmitting material and the coating layer reduce light reflection and light scattering, making it easier for light to transmit, and the light absorption rate of the phosphor particles can be increased. When the refractive index gradually decreases in the order of the phosphor particles, the coating layer, and the light-transmitting material, even when the light absorbed by the phosphor particles is wavelength-converted and emitted to the outside of the light-emitting device, the wavelength-converted light easily transmits through the coating layer and the light-transmitting material, and a high luminous flux of light can be emitted from the light-emitting device.When the light-transmitting material contained in the wavelength conversion member is a resin, for example, a silicone resin, the refractive index of the silicone resin when irradiated with light having a wavelength of 632.8 nm is about 1.40 to about 1.55, and when the coating layer is an oxide phase made of oxides and the oxide layer is silicon dioxide, the refractive index is close to that of the coating layer. When the light-transmitting material contained in the wavelength conversion member is a resin, for example, an epoxy resin, the refractive index of the epoxy resin when irradiated with light having a wavelength of 589.3 nm is 1.55 to 1.61.

[0014] The β-sialon phosphor preferably has a coating layer disposed on the entire surface of the phosphor particle having the composition represented by formula (I). When a coating layer is disposed on the entire surface of the phosphor particle, light irradiated from an excitation light source passes through the coating layer and enters the phosphor particle, so that reflection and scattering of light are reduced on the entire surface of the phosphor particle, the light absorption rate is increased, and the phosphor particle converts the wavelength of the light incident with high absorption rate, allowing light with high brightness to be emitted.

[0015] In the formula (I), the variable y represents the molar ratio of europium, which is the activating element of the β-sialon phosphor having the composition represented by the formula (I). The "molar ratio" refers to the molar amount of each element in 1 mole of the chemical composition. In the formula (I), the variable z represents the molar ratio of aluminum or oxygen. In the composition represented by the formula (I), the variable y represents the molar ratio of Eu, which is the activating element. The variable y is greater than 0 and less than or equal to 1.0 (0 < y ≤ 1.0), may be in the range of 0.0001 or more and 0.5 or less (0.0001 ≤ y ≤ 0.5), may be in the range of 0.0005 or more and 0.1 or less (0.0005 ≤ y ≤ 0.1), or may be in the range of 0.001 or more and 0.1 or less (0.001 ≤ y ≤ 0.1). In the formula (I), the variable z represents the molar ratio of Al or O. In the composition represented by the formula (I), the variable z is greater than 0 and less than or equal to 4.2 (0 < z ≤ 4.2), may be in the range of 0.0001 or more and 1.0 or less (0.0001 ≤ z ≤ 1.0), may be in the range of 0.0001 or more and 0.8 or less (0.0001 ≤ z ≤ 0.8), may be in the range of 0.0005 or more and 0.5 or less (0.0005 ≤ z ≤ 0.5), or may be in the range of 0.001 or more and 0.25 or less (0.001 ≤ z ≤ 0.25).

[0016] The β-sialon phosphor is measured by ICP-AES, and when the total of the phosphor particles and the coating layer is 100 mass%, if the coating layer is 0.4 mass% or more, the coating layer is formed on the entire surface of the phosphor particles. The β-sialon phosphor is measured by ICP-AES, and when the total of the phosphor particles and the coating layer is 100 mass%, the coating layer may be 0.5 mass% or more, 0.8 mass% or more, 1.0 mass% or more, 5.0 mass% or less, 4.0 mass% or less, 3.5 mass% or less, or 3.0 mass% or less. Considering that the light emitted from the excitation light source is transmitted through the coating layer to reach the phosphor particles and the light absorption of the phosphor particles is increased, the oxidized layer is preferably 5.0 mass% or less with respect to the total of the phosphor particles and the coating layer being 100 mass%. The coating layer of the β-sialon phosphor can be measured by ICP-AES using an inductively coupled plasma optical emission spectrometer (for example, Optima 8300, manufactured by Perkin Elmer).

[0017] When the coating layer is an oxide layer made of an oxide, the oxide preferably contains at least one element selected from the group consisting of silicon, aluminum, zirconium, and yttrium. A coating layer made of an oxide containing at least one element selected from the group consisting of silicon, aluminum, zirconium, and yttrium is easy to arrange on the coating layer having a refractive index smaller than that of the phosphor particles having the composition represented by the formula (I). For example, in the case of a coating layer made of an oxide containing silicon, when the oxide is silicon dioxide, the refractive index of the coating layer is in the range of 1.45 to 1.50 when irradiated with light having a wavelength of 380 nm to 780 nm. For example, in the case of a coating layer made of an oxide containing aluminum, when the oxide is aluminum oxide, the refractive index of the coating layer is in the range of 1.65 to 1.80 when irradiated with light having a wavelength of 380 nm to 780 nm. For example, in the case of a coating layer made of an oxide containing zirconium, when the coating layer is made of zirconium oxide, the refractive index of the coating layer is in the range of 1.95 to 2.05 when irradiated with light having a wavelength of 380 nm to 780 nm. For example, in the case of a coating layer made of an oxide containing yttrium, when the oxide is yttrium oxide, the refractive index of the coating layer is in the range of 1.85 to 1.95 when irradiated with light having a wavelength of 380 nm to 780 nm. When the coating layer is an oxide layer made of an oxide, the coating layer may contain at least two elements selected from the group consisting of silicon, aluminum, zirconium and yttrium, but it is preferable that the coating layer is made of an oxide containing one element.

[0018] The β-sialon phosphor has an average particle size D of 1 μm or more and 40 μm or less as measured by a Fisher Sub-Sieve Sizer (hereinafter, also referred to as “FSSS”) method, and a BET specific surface area of ​​2.5 m 2 The β-sialon phosphor has an average particle diameter D measured by the FSSS method in the range of 1 μm to 40 μm, and a BET specific surface area of ​​2.5 m 2 / g or more, it is considered that a film-like coating layer is disposed on the entire surface of the phosphor particle. The β-sialon phosphor has an average particle diameter D measured by the FSSS method in the range of 1 μm to 40 μm, a BET specific surface area of ​​20 m 2 / g or less, and 2.5m 2 / g or more 20m 2 / g or less. It is presumed that the β-sialon phosphor is present on the surface of phosphor particles having the composition represented by the formula (I) in the form of a film of dense silicon dioxide layers, for example, laminated thereon, and that very fine irregularities exist on the surface of the coating layer. A β-sialon phosphor having a coating layer disposed on the surface of a phosphor particle has a BET specific surface area of ​​2.5 m compared to phosphor particles not having a coating layer or phosphor particles having granular oxide disposed on the surface. 2 / g or more.

[0019] The FSSS method is a type of air permeability method, and is a method for measuring the specific surface area by utilizing the air flow resistance, and determining the particle size of the primary particles. The average particle size measured by the FSSS method is the Fisher Sub-Sieve Sizer's Number. The average particle size D by the FSSS method can be measured, for example, using Fisher Sub-Sieve Sizer Model 95 (manufactured by Fisher Scientific).

[0020] The β-sialon phosphor may have an average particle size measured by the FSSS method in the range of 2 μm to 38 μm, 3 μm to 35 μm, 5 μm to 35 μm, 5 μm to 30 μm, 25 μm or less, 20 μm or less, or 15 μm or less. The β-sialon phosphor having a coating layer disposed on the surface of the phosphor particle has an average particle size D measured by the FSSS method in the range of 5 μm to 35 μm, and a BET specific surface area of ​​2.5 m 2 / g or more 20m 2 / g or less, and 2 / g or more 18m 2 / g or less, and 2 / g or more 15m 2 The β-sialon phosphor having a coating layer disposed on the surface of the phosphor particle has an average particle diameter D measured by the FSSS method in the range of 8 μm to 20 μm, and a BET specific surface area of ​​2.5 m 2 / g or more 20m 2 / g or less, and2 / g or more 18m 2 / g or less, and 2 / g or more 15m 2 The β-sialon phosphor has an average particle size D of 8 μm or more and 15 μm or less as measured by the FSSS method, and a BET specific surface area of ​​2.5 m 2 / g or more 20m 2 / g or less, and 2 / g or more 18m 2 / g or less, and 2 / g or more 15m 2 / g or less.

[0021] The phosphor particles having the composition represented by formula (I) have a β-sialon composition and are better in moisture resistance than nitride phosphors having a composition different from that of β-sialon. Since the phosphor having the β-sialon composition represented by formula (I) has good moisture resistance, the phosphor may be improved in dispersibility by disposing granular materials such as colloidal silica on the surface of the phosphor particles, instead of covering the entire surface of the phosphor with a film-like coating film, as in the case of nitride phosphors having a composition different from that of β-sialon represented by formula (I). When granular materials such as colloidal silica are disposed on the surface of the phosphor particles, the BET specific surface area is 2.5 m even if the average particle size measured by the FSSS method is within the range of 1 μm to 40 μm. 2 / g, and the BET specific surface area of ​​β-sialon phosphors with an average particle size D of 1 μm or more and 40 μm or less measured by the FSSS method is 2.5 m 2 / g or less, 2.5m 2 / g, and 2.0m 2 / g or less, 1.5m 2 / g or less, 1.0m 2 / g or less.

[0022] The β-sialon phosphor preferably has a particle size ratio D / Dm of 0.6 or more, where D is the volume median diameter Dm measured by the laser diffraction particle size distribution measurement method and D is the average particle size D measured by the FSSS method. The laser diffraction particle size distribution measurement method is a method for measuring particle size without distinguishing between primary and secondary particles by using scattered light of a laser beam irradiated onto a particle. The volume median diameter Dm measured by the laser diffraction particle size distribution measurement method is the value at which the volume cumulative frequency from the small diameter side in the volume-based particle size distribution measured by the laser diffraction particle size distribution measurement method reaches 50%. The laser diffraction particle size distribution measurement method can be performed using, for example, a laser diffraction particle size distribution measurement device (MASTER SIZER 3000, manufactured by MALVERN).

[0023] The closer the particle size ratio D / Dm of the average particle size D measured by the FSSS method to the volume median size Dm measured by the laser diffraction particle size distribution measurement method is to 1, the fewer the phosphor particles are aggregated, the more primary particles are contained, and the better the dispersibility is. When using a β-sialon phosphor in a light-emitting device, the β-sialon phosphor is dispersed in a light-transmitting material such as a resin and used as a wavelength conversion member, so it is preferable that the β-sialon phosphor has good dispersibility. Since a β-sialon phosphor having a coating layer on the surface of the phosphor particle has high absorption of irradiated light as described above, the particle size ratio D / Dm does not need to be as large as 1.0. The particle size ratio D / Dm of the β-sialon phosphor is preferably 0.6 or more, more preferably 0.65 or more, and even more preferably 0.7 or more. β-sialon phosphors that do not have a coating layer on the surface of the phosphor particles, or β-sialon phosphors that have a granular oxide such as colloidal silica on the surface of the phosphor particles, have good dispersibility and may have a particle size ratio D / Dm that exceeds 0.9 and approaches 1.0. However, even if they have good dispersibility, they do not have a high light absorption rate compared to β-sialon phosphors that have a coating layer on the surface of the phosphor particles, and therefore may not emit light with high brightness.

[0024] When the average particle size D measured by the FSSS method is in the range of 1 μm to 40 μm, and the particle size ratio D / Dm is 0.6 or more, the volume median diameter Dm measured by the laser diffraction particle size distribution measurement method may be in the range of 1.66 μm to 66 μm. When the particle size ratio D / Dm of the β-sialon phosphor is 0.6 or more, the volume median diameter Dm may be in the range of 3 μm to 65 μm, 5 μm to 60 μm, 8 μm to 55 μm, 50 μm or less, 45 μm or less, or 40 μm or less.

[0025] The thickness of the coating layer of the β-sialon phosphor is preferably in the range of 50 nm to 200 nm. The thickness of the coating layer of the β-sialon phosphor may be in the range of 60 nm to 180 nm, or may be in the range of 60 nm to 150 nm. The thickness of the coating layer can be derived by a measurement method described later. When the thickness of the coating layer of the β-sialon phosphor is in the range of 50 nm to 200 nm, the coating layer reduces light reflection and light scattering, making it easier for light to transmit, and increasing the light absorption rate of the phosphor particles, allowing the β-sialon phosphor to emit light with high brightness. In addition, when the thickness of the coating layer of the β-sialon phosphor is in the range of 50 nm to 200 nm, a light emitting device containing the β-sialon phosphor can emit light with high luminous flux.

[0026] The thickness of the coating layer of the β-sialon phosphor can be measured as follows. The cross-sectional image of a single β-sialon phosphor is divided into two or more sections, and in the cross-sectional image of the β-sialon phosphor of one of the two or more sections, the line indicating the inside of the coating layer is defined as the inner line, the line indicating the outside of the coating layer is defined as the outer line, the line connecting one end of the inner line to one end of the outer line is defined as the first end line, and the line connecting the other end of the inner line to the other end of the outer line is defined as the second end line. The thickness of the coating layer is calculated from the area of ​​the coating layer enclosed by the inner line, the outer line, the first end line, and the second end line relative to the average value of the sum of the lengths of the inner line and the outer line using the following formula (1). The total value of the thickness of the coating layer in each section calculated in the sectioned cross section is divided by the number of sections into which the cross section of a single β-sialon phosphor is divided, and the average value of the thickness of the coating layer can be determined as the thickness of the coating layer of the β-sialon phosphor. Thickness of coating layer = [Area of ​​coating layer at cross section ÷ (Length of outer line of coating layer + Length of inner line of coating layer) / 2] (1)

[0027] The cross-sectional image of the β-sialon phosphor can be obtained by embedding the β-sialon phosphor in a resin, hardening the resin, cutting the resin so that the cross-section is exposed, polishing the surface with sandpaper, and finishing the surface with a cross-section polisher (CP), and then using a field emission scanning electron microscope (FE-SEM) to obtain an SEM photograph. The resin for embedding the β-sialon phosphor is preferably an epoxy resin so that the cross-section of the β-sialon phosphor can be easily distinguished. The cross-sectional image of one β-sialon phosphor may be obtained at a magnification of, for example, 5000 to 50000 times so that the thickness of the coating layer can be measured as described above, and the image of the cross-section of one β-sialon phosphor is preferably divided into two or more sections, and depending on the size of one β-sialon phosphor, the image of the cross-section of one β-sialon phosphor is preferably divided into 2 to 10 sections, may be divided into 3 to 8 sections, or may be divided into 3 to 7 sections. Typically, a β-sialon phosphor is selected from a cross section passing through the center or near the center of the phosphor core observed at a magnification of 5,000 to 50,000 times using a field emission scanning electron microscope (FE-SEM). Also, a section is selected from a section in which the inner and outer lines of the coating layer are visible within the above magnification range.

[0028] When irradiated with light having a peak emission wavelength in the range of 380 nm to 500 nm, the β-sialon phosphor emits light having a peak emission wavelength in the range of 520 nm to 560 nm.

[0029] The β-sialon phosphor can be used in a light-emitting device. The light-emitting device includes a wavelength conversion member including the above-mentioned β-sialon phosphor and a light-transmitting material, and a light-emitting element having an emission peak wavelength in the range of 380 nm to 500 nm. The light-transmitting material is preferably such that the difference between the refractive index of the light-transmitting material and the refractive index of the coating layer of the β-sialon phosphor is in the range of 0.01 to 0.80 in absolute value. It is more preferable that the refractive index of the light-transmitting material of the wavelength conversion member is smaller than the refractive index of the coating layer of the β-sialon phosphor. If the difference between the refractive index of the light-transmitting material of the wavelength conversion member and the refractive index of the coating layer of the β-sialon phosphor is small, light reflection and scattering are reduced, light is more easily transmitted, the light absorption rate of the phosphor particles is increased, and a high luminous flux of light can be emitted from the light-emitting device. If the refractive index of the translucent material of the wavelength conversion member is smaller than the refractive index of the coating layer of the β-sialon phosphor, the reflection and scattering of light from the excitation light source is further reduced, making it easier for light to transmit, and increasing the light absorption rate of the phosphor particles, allowing the light emitting device to emit light with a higher luminous flux.

[0030] FIG. 1 is a schematic cross-sectional view showing an example of a light emitting device.

[0031] The light emitting device 100 includes a package having a recess formed by the lead electrodes 20, 30 and the molded body 40, a light emitting element 10, and a wavelength conversion member 50 covering the light emitting element 10. The light emitting element 10 is disposed in the recess of the package, and is electrically connected to a pair of positive and negative lead electrodes 20, 30 provided on the molded body 40 by a conductive wire 60. The wavelength conversion member 50 is filled in the recess of the package, covers the light emitting element 10, and seals the recess of the package. The wavelength conversion member 50 includes, for example, a phosphor 70 that converts the wavelength of light from the light emitting element 10, and a resin, and is formed to cover the light emitting element 10 placed in the recess of the light emitting device 100. The phosphor 70 includes a first phosphor 71 as a β-sialon phosphor, and may include a second phosphor 72 having a different composition from the β-sialon phosphor. The pair of positive and negative lead electrodes 20, 30 are partially exposed on the outer surface of the package. When power is supplied from the outside via these lead electrodes 20, 30, the light emitting device 100 emits light.

[0032] A light-emitting element can be used as an excitation light source for the light-emitting device. The light-emitting element has an emission peak wavelength in the range of 380 nm to 500 nm, preferably in the range of 400 nm to 480 nm, more preferably in the range of 420 nm to 470 nm, and may be in the range of 420 nm to 460 nm. By using a light-emitting element having an emission peak wavelength in the range of 380 nm to 500 nm as an excitation light source, a mixed color light of the light from the light-emitting element and the fluorescence from the phosphor is emitted.

[0033] The light-emitting element is a nitride semiconductor (In X Al Y Ga 1-X-Y It is preferable to use a semiconductor light-emitting element using a semiconductor light-emitting element having a wavelength of 0≦X, 0≦Y, X+Y≦1. By using a semiconductor light-emitting element as an excitation light source for a light-emitting device, it is possible to obtain a highly efficient light-emitting device with high linearity of output relative to input and high mechanical shock resistance. The full width at half maximum of the emission spectrum of the light-emitting element is preferably, for example, 30 nm or less.

[0034] The light emitting device includes the aforementioned β-sialon phosphor. The β-sialon phosphor preferably has phosphor particles having a composition represented by formula (I) and is excited with light in a wavelength range of 380 nm to 500 nm to emit fluorescence having an emission peak wavelength in a range of 520 nm to 560 nm. The light emitting device may include a first phosphor including the β-sialon phosphor, and a second phosphor having a different composition from the β-sialon phosphor and emitting fluorescence having an emission peak wavelength different from the emission peak wavelength of the first phosphor.

[0035] The first phosphor can be contained in a wavelength conversion member that covers the excitation light source to form a light emitting device. In a light emitting device in which the excitation light source is covered with a wavelength conversion member that contains the first phosphor, a part of the light emitted from the excitation light source is absorbed by the first phosphor, and fluorescence having an emission peak wavelength at a wavelength different from the emission peak wavelength of the light emitted from the excitation light source is emitted.

[0036] The content of the first phosphor in the light emitting device is not particularly limited. For example, the content of the first phosphor can be 1 part by mass or more and 200 parts by mass or less, and preferably 2 parts by mass or more and 180 parts by mass or less, per 100 parts by mass of the resin constituting the wavelength conversion member.

[0037] The first phosphor and / or the second phosphor (hereinafter, simply referred to as "phosphors") can form a wavelength conversion member that covers the light-emitting element together with a light-transmitting material. The light-transmitting material that forms the wavelength conversion member can be a resin, and examples of the resin include silicone resin and epoxy resin.

[0038] The wavelength conversion member may further contain a filler, a light diffusing material, etc., in addition to the light-transmitting material and the phosphor. For example, by containing a light diffusing material, the directivity from the light-emitting element can be alleviated and the viewing angle can be increased. Examples of the filler include silica, titanium oxide, zinc oxide, zirconium oxide, alumina, etc. When the wavelength conversion member contains a filler, the content thereof can be appropriately selected depending on the purpose, etc. The content of the filler can be, for example, 1% by mass or more and 20% by mass or less with respect to the resin.

[0039] Next, a method for producing the β-sialon phosphor will be described. The method for producing a β-sialon phosphor preferably includes preparing phosphor particles having a composition represented by formula (I) and disposing a coating layer on the surface of the phosphor particles. The method for producing a β-sialon phosphor may include dispersing the phosphor particles after obtaining the phosphor particles and before disposing the coating layer. The method for producing a β-sialon phosphor may include washing the obtained phosphor particles after obtaining the phosphor particles and before disposing the coating layer. When the method for producing a β-sialon phosphor includes dispersing the phosphor particles, it is preferable to include washing the phosphor particles before dispersing the phosphor particles in a liquid, and it is more preferable to include washing and dispersing the phosphor particles. The method for producing a β-sialon phosphor may include drying the obtained β-sialon phosphor after disposing the coating layer on the surface of the phosphor particles. It may include performing a heat treatment after disposing the coating layer on the surface of the phosphor particles. The method for producing a β-sialon phosphor may include re-dispersing the obtained β-sialon phosphor after disposing the coating layer on the surface of the phosphor particles.

[0040] 2 to 4 are flow charts showing an example of a method for producing a β-sialon phosphor. As shown in FIG. 2, the method for producing a β-sialon phosphor preferably includes preparing phosphor particles S101 and disposing a coating layer on the surface of the phosphor particles S103. The method for producing a β-sialon phosphor may include washing and dispersing the phosphor particles S102 after preparing phosphor particles S101 and before disposing a coating layer on the surface of the phosphor particles S103 as shown in FIG. 3. The method for producing a β-sialon phosphor may include redispersing the obtained β-sialon phosphor S104 after disposing a coating layer on the surface of the phosphor particles S103 as shown in FIG. 4.

[0041] The preparation of the phosphor particles includes firing the raw material mixture to prepare a fired product having a composition represented by the formula (I), pulverizing the fired product to obtain a pulverized product, and heat-treating the pulverized product to obtain a heat-treated product, and the steps of obtaining the pulverized product and obtaining the heat-treated product may be repeated two or more times in this order. The preparation of the phosphor particles can be performed by referring to the method described in JP 2019-135312 A. The phosphor particles may be commercially available products.

[0042] The raw material mixture is obtained by mixing an aluminum-containing compound, metallic europium or a compound containing europium, and silicon nitride so that each element contained in the compound or metallic europium satisfies the composition represented by the above formula (I). 2 O 3 , Al(OH) 2 Examples of compounds containing europium include Eu 2 O 3 , EuN, EuF 3The average particle size of the metal or compound used as the raw material may be a size that is normally present as a powder, for example, 0.01 μm to 20 μm. The raw material mixture may contain a flux such as a halide, if necessary. By containing the flux, the raw material mixture is more promoted in the reaction between the raw materials, and the solid-phase reaction proceeds uniformly. As the halide, a chloride or fluoride of a rare earth metal, an alkaline earth metal, or an alkali metal can be used. The raw material mixture preferably contains each compound such that the elements in each compound contained in the raw material mixture satisfy the molar ratio of each element in the composition represented by the formula (I).

[0043] In preparing phosphor particles, the raw material mixture is fired to prepare a fired product by firing the raw material mixture at a temperature of preferably 1850° C. to 2100° C. in an atmosphere containing nitrogen gas at atmospheric pressure (approximately 0.1 MPa) to 200 MPa to obtain a fired product. The nitrogen gas-containing atmosphere preferably has a nitrogen gas content of 90% by volume or more, more preferably 95% by volume or more.

[0044] In preparing phosphor particles, the obtained fired product is crushed to obtain a crushed product, which may not only be a coarse crushing or disintegration of powder aggregates of the fired product powder, but may also be a strong crushing until the fired product becomes a crushed product of a predetermined size. The fired product may be crushed using a dry crusher such as a ball mill, a vibration mill, a hammer mill, a roll mill, or a jet mill. In obtaining a crushed product, the fired product may be crushed together with a compound containing an activator element that becomes an activator element of the phosphor particles. When the crushing and the heat treatment are performed in this order two or more times, the fired product may be crushed together with a compound containing an activator element that becomes an activator element of the phosphor particles in the second crushing.

[0045] In preparing phosphor particles, the heat treatment of the obtained pulverized material to obtain a heat-treated material is preferably performed at a temperature of 1850°C to 2100°C, in an inert gas atmosphere, and at a pressure of atmospheric pressure (about 0.1 MPa) to 200 MPa to obtain a heat-treated material. The inert gas atmosphere means an atmosphere containing argon, helium, nitrogen, etc. as the main component in the atmosphere. The inert gas atmosphere may contain oxygen as an unavoidable impurity, but here, it is considered to be an inert gas atmosphere if the concentration of oxygen contained in the atmosphere is 15 volume % or less. In heat treating the pulverized material, the heat treatment of the pulverized material may be performed together with a compound containing an activating element that becomes an activating element of the phosphor particles. In the present specification, in preparing phosphor particles, the heat treatment of the pulverized material may be referred to as the first heat treatment. In preparing phosphor particles, even if the pulverization of the fired material and the heat treatment of the pulverized material are performed in this order two or more times, the heat treatment performed to prepare the phosphor particles is referred to as the first heat treatment.

[0046] The preparation of phosphor particles may include annealing the heat-treated product in a rare gas atmosphere at a temperature lower than the heat treatment temperature in obtaining the heat-treated product to obtain an annealed product. The rare gas atmosphere may contain at least one rare gas such as helium, neon, argon, etc., and preferably contains at least argon. The rare gas atmosphere may contain oxygen, hydrogen, nitrogen, etc. in addition to the rare gas. The content of the rare gas in the rare gas atmosphere is preferably 95% by volume or more, more preferably 99% by volume or more.

[0047] The phosphor particles are washed by contacting the obtained phosphor particles with an acidic solution or a basic solution and washing them. After contacting the phosphor particles with an acidic solution or a basic solution, the phosphor particles may be washed with a liquid such as ion-exchanged water. By contacting the phosphor particles with an acidic solution or a basic solution, decomposition products contained in the phosphor particles that are decomposed during the second heat treatment can be removed. In washing the phosphor particles, the acidic solution may be an acidic solution containing an inorganic acid such as hydrofluoric acid or nitric acid, or an acidic substance such as hydrogen peroxide. In washing the phosphor particles, the basic solution may be a basic solution containing a basic substance such as a hydroxide containing an alkali metal or ammonia. The basic substance may be, specifically, LiOH, NaOH, KOH, RbOH, CsOH, and NH 3 The phosphor particles may be contacted with an acidic or basic solution for 10 minutes or more and 30 hours or less, or may be contacted with an acidic or basic solution for 1 hour or more and 25 hours or less. The temperature at which the phosphor particles are contacted with the acidic or basic solution may be in the range of room temperature (about 20°C) or more and 300°C or less, or in the range of 30°C or more and 200°C or less, or in the range of 40°C or more and 150°C or less, in order to obtain phosphor particles from which decomposition products contained in the heat treatment product have been efficiently removed. After contacting the phosphor particles with the acidic or basic solution, they may be further washed with a liquid medium. An example of the liquid medium is deionized water. The time for washing with the liquid medium is, for example, 10 minutes or more and 30 hours or less, or may be 30 minutes or more and 25 hours or less.

[0048] In the method for producing a β-sialon phosphor, washing the phosphor particles may include crushing, pulverizing, or classifying the phosphor particles after the washing step, and drying the phosphor particles. As the classifying step, it is preferable to carry out at least one of wet dispersion, wet sieving, dehydration, drying, and dry sieving. The drying temperature is preferably 60°C or higher and 120°C or lower.

[0049] In the method for producing a β-sialon phosphor, dispersing phosphor particles means dispersing the obtained phosphor particles in a liquid. The liquid in which the phosphor particles are dispersed may be deionized water or a liquid containing at least one selected from the group consisting of ethanol, 1-propanol, and 2-propanol. The liquid may contain a catalyst such as ammonia.

[0050] In disposing a coating layer on the surface of the phosphor particles, it is preferable to dispose the coating layer on the surface of the phosphor particles by contacting the phosphor particles with a solution containing a metal alkoxide. A solution containing a metal alkoxide may be dropped into a reaction solution, which is a liquid in which phosphor particles are dispersed, to cause a hydrolysis reaction between the phosphor particles and the metal alkoxide, thereby disposing a coating layer on the surface of the phosphor particles. When a solution containing a metal alkoxide is dropped onto phosphor particles dispersed in a liquid to cause a hydrolysis reaction, a coating layer can be disposed on the entire surface of the phosphor particles.

[0051] In disposing a coating layer on the surface of the phosphor particles, the temperature at which the phosphor particles are brought into contact with the solution containing a metal alkoxide is a temperature near room temperature, and in order to prevent the solution containing the metal alkoxide from solidifying, the temperature is preferably higher than the freezing point temperature of the solvent contained in the solution containing the metal alkoxide and / or the solvent contained in the reaction solution containing the phosphor particles. The temperature near room temperature at which the phosphor particles are brought into contact with the solution containing a metal alkoxide is about 25° C., and is between 15° C. and 35° C. The temperature at which the phosphor particles are brought into contact with the solution containing a metal alkoxide may be greater than 0° C. and not greater than 70° C., or greater than 0° C. and not greater than 50° C.

[0052] When disposing a coating layer on the surface of the phosphor particle, in order to increase the coverage rate of the coating layer relative to the surface of the phosphor particle, the time for which the phosphor particle is contacted with the solution containing a metal alkoxide is preferably 1 hour or more, may be 1.5 hours or more, may be 2 hours or more, or preferably 5 hours or more, and may be 24 hours or less in order to improve productivity.

[0053] The metal alkoxide is a metal alkoxide containing at least one element selected from the group consisting of silicon, aluminum, zirconium, and yttrium. The metal alkoxide is preferably a silane compound having two or more alkoxyl groups. Specific examples of the metal alkoxide include methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, aluminum triethoxide, aluminum tripropoxide, aluminum tribudoxide, aluminum triisopropoxide, zirconium tetrapropoxide, zirconium tetrabutoxide, yttrium (III) isopropoxide, and yttrium (III) butoxide. In consideration of workability and availability, the metal alkoxide is preferably tetraethoxysilane.

[0054] The phosphor particles are brought into contact with a solution containing a metal alkoxide, and the metal alkoxide is hydrolyzed and polycondensed, so that a coating layer is formed on the surface of the phosphor particles. For example, the metal alkoxide is tetraethoxysilane (Si(OC 2 H 5 ) 4 ), the phosphor particles are treated with tetraethoxysilane (Si(OC 2 H 5 ) 4 ) to hydrolyze tetraethoxysilane, thereby obtaining orthosilicic acid (Si(OH) 4 ) is formed, and orthosilicic acid (Si(OH) 4 ) undergoes a dehydration reaction due to condensation polymerization, resulting in the formation of silicon dioxide (SiO 2 A coating layer containing silicon dioxide (SiO ) is disposed on the surface of the phosphor particles. The coating layer is formed by hydrolysis and polycondensation of tetraethoxysilane. 2 The coating layer may also contain a silicon compound having residual hydroxyl groups (OH) in part.

[0055] The solution containing the metal alkoxide preferably contains an amount of metal alkoxide such that the coating layer obtained by hydrolysis and condensation polymerization of the metal alkoxide is 0.4% by mass or more relative to the total 100% by mass of the phosphor particles and the coating layer. The solution containing the metal alkoxide may contain an amount of metal alkoxide such that the coating layer obtained by hydrolysis and condensation polymerization of the metal alkoxide is 5.0% by mass or less relative to the total 100% by mass of the phosphor particles and the coating layer. The solution containing the metal alkoxide may contain an amount of metal alkoxide such that the coating layer obtained by hydrolysis and condensation polymerization of the metal alkoxide is 0.5% by mass or more, 0.8% by mass or more, 1.0% by mass or more, 4.0% by mass or less, 3.5% by mass or less, or 3.0% by mass or less relative to the total 100% by mass of the phosphor particles and the coating layer.

[0056] In disposing a coating layer on the surface of the phosphor particles, the coating layer may be formed, for example, by a sol-gel method, a chemical vapor deposition (CVD) method using a solution containing a metal alkoxide, or an atomic layer deposition (ALD) method using a solution containing a metal alkoxide.

[0057] In disposing a coating layer on the surface of the phosphor particles, it is preferable to have a basic catalyst present when the phosphor particles are brought into contact with a solution containing a metal alkoxide. By having a basic catalyst present when the phosphor particles are brought into contact with a solution containing a metal alkoxide, the hydrolysis and polycondensation reactions of the metal alkoxide can be promoted even at a low temperature below the ambient temperature, and a coating layer can be disposed on the surface of the phosphor particles with a high coverage rate. The basic catalyst is not particularly limited, but at least one selected from the group consisting of ammonium, ammonium carbonate, ammonium hydrogen carbonate, ammonium formate, ammonium acetate, sodium carbonate, and sodium hydrogen carbonate can be used. The basic catalyst may be added to a reaction solution in which the phosphor particles are dispersed, so that the basic catalyst is present when the phosphor particles are brought into contact with a solution containing a metal alkoxide. The basic catalyst may be added to a solution containing a metal alkoxide, so that the basic catalyst is present when the phosphor particles are brought into contact with a solution containing a metal alkoxide. When the basic catalyst is added to the reaction solution or the solution containing the metal alkoxide, the compound that serves as the basic catalyst may be added to each solution in the range of 0.001 mol / L or more and 1.0 mol / L or less.

[0058] The solution containing the metal alkoxide preferably contains water and / or alcohol. The solution containing the metal alkoxide preferably contains water and / or alcohol as a solvent. The water may be deionized water. The alcohol may be at least one selected from the group consisting of methanol, ethanol, 1-propanol, and 2-propanol.

[0059] In the method for producing a β-sialon phosphor, the coating layer may be disposed on the surface of the phosphor particles two or more times. That is, the method may include contacting the phosphor particles with a solution containing a metal alkoxide two or more times. When the method includes contacting the phosphor particles with a solution containing a metal alkoxide two or more times, the phosphor particles may be contacted with the solution containing a metal alkoxide two or more times, three or more times, or five or less times, so that the coating layer is within the range of 0.4 mass% to 5.0 mass% relative to the total of 100 mass% of the phosphor particles and the coating layer. When the phosphor particles are contacted with the solution containing a metal alkoxide two or more times, the contact temperature is equal to or lower than the ambient temperature.

[0060] The method for producing a β-sialon phosphor may include forming a coating layer on the surface of the phosphor particle and further performing a heat treatment on the phosphor particle and the coating layer disposed on the surface in disposing the coating layer on the surface of the phosphor particle. In this specification, the heat treatment of the phosphor particle and the coating layer disposed on the surface of the phosphor particle may be referred to as a second heat treatment. The temperature of the second heat treatment is preferably more than 250°C and less than 500°C. By disposing a coating layer on the surface of the phosphor particle and performing a heat treatment (second heat treatment), a dehydration reaction proceeds in the coating layer containing hydroxyl groups (OH), and a β-sialon phosphor in which the coating layer is firmly attached to the surface of the phosphor particle is obtained. The oxygen in the coating layer also acts on the phosphor particle and bonds with an element (Si or Al) derived from the phosphor particle, and the coating layer is disposed more firmly bonded to the phosphor particle. The temperature of the heat treatment (second heat treatment) performed by disposing a coating layer on the surface of the phosphor particles may be more than 250°C and less than 500°C, more than 250°C and less than 450°C, or more than 300°C and less than 400°C. The second heat treatment is preferably performed in air or in an inert gas atmosphere. By performing the second heat treatment in air or an inert gas atmosphere on a β-sialon phosphor having a coating layer disposed on the surface of the phosphor particles, a dehydration reaction proceeds in the coating layer containing hydroxyl groups (OH), and a part of the elements (e.g., Si) contained in the coating layer is more strongly bonded to the elements (e.g., Si or Al) derived from the phosphor particles via oxygen. The time of the second heat treatment is not particularly limited, but may be 1 hour or more and less than 20 hours, 2 hours or more and less than 15 hours, or 3 hours or more and less than 10 hours. If the time for the second heat treatment is 1 hour or more and 20 hours or less, the second heat treatment does not affect the phosphor particles, the amount of hydroxyl groups (OH) contained is small, and the coating layer can be arranged in close contact with the surface of the phosphor particles. The method for producing a β-sialon phosphor may include a post-treatment such as crushing, grinding, or classification of the obtained heat-treated product, phosphor particles, or β-sialon phosphor after each of the first heat treatment and the second heat treatment.

[0061] The method for producing a β-sialon phosphor may include distributing the resulting β-sialon phosphor after disposing a coating layer on the surface of the phosphor particles. By redispersing the β-sialon phosphor having a coating layer on the surface of the phosphor particles, aggregation of the β-sialon phosphor having a coating layer on the surface of the phosphor particles can be reduced, and a β-sialon phosphor having good dispersibility in a light-transmitting material can be obtained when manufacturing a light-emitting device. In the method for producing a β-sialon phosphor, redispersing the β-sialon phosphor specifically means dispersing the β-sialon phosphor in a liquid. The liquid in which the β-sialon phosphor is dispersed may be the same liquid as the liquid in which the phosphor particles are dispersed. Redispersing the β-sialon phosphor may include at least one of wet dispersion, wet sieving, dehydration, drying, and dry sieving. The time for redispersing the β-sialon phosphor is preferably 1 hour or more and 10 hours or less, may be 2 hours or more and 8 hours or less, or may be 3 hours or more and 6 hours or less.

[0062] The method of preparing the β-sialon phosphor may include removing the β-sialon phosphor from the liquid after redispersing the β-sialon phosphor, and drying the β-sialon phosphor. When the β-sialon phosphor is dried after redispersion, at least one element selected from the group consisting of silicon, aluminum, zirconium, and yttrium is bonded to the surface of the phosphor particles in a state containing a hydroxyl group (OH), and then drying removes hydrogen from the hydroxyl group (OH) to arrange the coating layer in a state of being in close contact with the surface of the phosphor particles. Drying can be performed using a device commonly used in industry, such as a hot air dryer, a vacuum dryer, a conical dryer, a rotary evaporator, or a spray dryer. The drying temperature is preferably within a range of 60° C. to 120° C. The drying time is not particularly limited, but is preferably 1 hour to 30 hours, more preferably 2 hours to 25 hours, and even more preferably 3 hours to 24 hours. EXAMPLES

[0063] The present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited to these examples.

[0064] Example 1 Preparing phosphor particles Silicon nitride (Si 3 N 4 ), aluminum nitride (AlN), and aluminum oxide (Al 2 O 3 ) and europium oxide (Eu 2 O 3 ) were weighed out so that the molar ratio of Si:Al:Eu was 5.79:0.21:0.011, and mixed to obtain a raw material mixture. 2 O 3 ) were weighed and mixed to a molar ratio of 75:25. This raw material mixture was filled into a boron nitride crucible and fired for 10 hours in a nitrogen atmosphere (nitrogen: 99% by volume or more) at 0.92 MPa (gauge pressure) and 2030°C to obtain a fired product. The obtained fired product was coarsely ground using a mortar and pestle, and then subjected to a first grinding process by strong grinding for 20 hours using a ball mill using two types of silicon nitride balls with diameters (Φ) of 20 mm and 25 mm and a porcelain pot to obtain a ground product. In the first grinding process, 1 mole of the fired product was mixed with 10000 europium oxide (Eu 2 O 3 ) was added thereto, and the mixture was ground. The obtained pulverized material was then loaded into a crucible made of boron nitride and subjected to a second heat treatment (second first heat treatment) for 10 hours in a nitrogen atmosphere (nitrogen: 99% by volume or more) at 0.92 MPa (gauge pressure) and 2000°C to obtain a heat-treated material. The heat-treated product was then subjected to a second pulverization process under the same conditions as the first pulverization process to obtain a pulverized product. In the second pulverization process, 1 mole of the heat-treated product was mixed with 1000 mg of europium oxide (Eu 2 O 3 ) was added in an amount of 0.002 mole, and the mixture was then ground. The resulting pulverized material was then loaded into a crucible made of boron nitride and subjected to a third heat treatment in a nitrogen atmosphere (nitrogen: 99% by volume or more), at 0.92 MPa (gauge pressure), and at 1980°C for 10 hours to obtain a heat-treated material, which was obtained as phosphor particles having the composition represented by formula (I) above.

[0065] Washing and dispersing phosphor particles The obtained phosphor particles were contacted with an aqueous sodium hydroxide solution containing 33% by mass of NaOH at 130°C for 20 hours, then washed with deionized water and dried. The particles were then crushed by wet dispersion, passed through a sieve, and stirred in deionized water to allow the phosphor to settle for a certain period of time, after which the supernatant was discarded for classification, and then dried at 90°C to 105°C. The drying temperature may be within the range of 60°C to 120°C. The dried phosphor particles were mixed with 180 mL of an alcohol preparation (Solmix AP-7) containing ethanol, 1-propanol, and 2-propanol, and 63 mL of ammonia water containing 11.0 mass% ammonia as a basic catalyst to prepare a reaction solution. 100 g of the obtained phosphor particles were added to the reaction solution and stirred at room temperature to disperse the phosphor particles.

[0066] Disposing a coating layer on the surface of the phosphor particles Tetraethoxysilane (Si(OC 2 H 5 ) 4 10.4 g of an ethanol solution (tetraethoxysilane concentration 28 mass%) of the phosphor particles was used as a solution containing a metal ion alkoxide. In the solution containing a metal alkoxide, the element contained in the coating layer was Si, and the solution containing a metal alkoxide had a ratio of SiO 2The reaction solution contained tetraethoxysilane with a content of 3.0 mass%. While stirring the reaction solution, the solution containing the metal alkoxide was dropped into the reaction solution over 150 minutes. After the dropwise addition of the solution containing the metal alkoxide was completed, the reaction solution was stirred for 60 minutes, and the phosphor particles and the solution containing the metal alkoxide were brought into contact with each other in the presence of ammonia, which is a basic catalyst. Thereafter, the stirring was stopped, and the phosphor particles having a coating layer formed on the surface thereof were taken out of the reaction solution, and dried in a dryer at a temperature of 60°C or higher and lower than 120°C for 15 hours or more to form a coating layer on the surface of the phosphor particles, thereby obtaining a β-sialon phosphor of Example 1. The β-sialon phosphor of Example 1 is composed of phosphor particles and an oxide (SiO 2 The coating layer has a refractive index in the range of about 1.45 to about 1.50 when irradiated with light having a wavelength in the range of 380 nm to 780 nm.

[0067] Example 2 Redispersing β-sialon phosphor 200 g of β-sialon phosphor obtained in the same manner as in Example 1 was crushed by wet dispersion. Specifically, the β-sialon phosphor was redispersed by placing it in a plastic bottle containing 200 g of deionized water and 250 g of polyethylene beads and rotating it to perform wet dispersion. After redispersing for 3 hours, the β-sialon phosphor was taken out and dried in a dryer at a temperature of 60° C. or higher and lower than 120° C. for 15 hours or more to obtain the β-sialon phosphor of Example 2.

[0068] Example 3 A β-sialon phosphor of Example 3 was obtained in the same manner as in Example 2, except that in redispersing the β-sialon phosphor in the liquid, the wet dispersion time was changed to 5 hours.

[0069] Comparative Example 1 The phosphor particles were prepared as β-sialon phosphors of Comparative Example 1 in the same manner as in Example 1, except that no coating layer was provided on the surfaces of the phosphor particles.

[0070] Comparative Example 2 100 g of phosphor particles were placed in 400 g of deionized water, and while stirring the phosphor particles, 0.15 mL of colloidal silica solution (silicon dioxide concentration 20 mass%) was dropped with a dropper, and then hydrochloric acid was added until the pH of the slurry became 2, and the mixture was stirred for another 5 minutes. After stirring for 5 minutes, an aqueous ammonia solution was added until the pH of the slurry became about 7 to neutralize it, stirring was stopped, the phosphor particles were allowed to settle, and the supernatant was discarded. Furthermore, the phosphor particles were washed with deionized water, and the process of settling the phosphor particles and discarding the supernatant was repeated once. Thereafter, the phosphor particles having granular colloidal silica disposed on their surfaces were taken out and dried in a dryer at a temperature of 60°C or higher and lower than 120°C for 15 hours or more, thereby obtaining a β-sialon phosphor of Comparative Example 2 having granular colloidal silica disposed on the surfaces of the phosphor particles.

[0071] The following evaluations were carried out for each β-sialon phosphor of the Examples and Comparative Examples. The results are shown in Table 1. In Table 1, the symbol "-" indicates that there is no corresponding item.

[0072] Average particle size D For each β-sialon phosphor of the examples and comparative examples, the average particle size D is measured by the FSSS method using a Fisher Sub-Sieve Sizer Model 95 (manufactured by Fisher Scientific).

[0073] Volume median diameter Dm For each β-sialon phosphor of the examples and comparative examples, the volume median diameter Dm at which the volume cumulative frequency from the small diameter side reaches 50% is measured using a laser diffraction particle size distribution measuring device (MASTER SIZER3000, manufactured by MALVERN).

[0074] Particle size ratio D / Dm The particle size ratio D / Dm of the average particle size D to the volume median size Dm is calculated.

[0075] Relative Luminance (%) The emission spectrum of each β-sialon phosphor of the examples and comparative examples was measured using a quantum efficiency measurement system (QE-2000, manufactured by Otsuka Electronics Co., Ltd.). The emission peak wavelength of the excitation light used in the quantum efficiency measurement system was 450 nm. The luminance was measured from each emission spectrum. The luminance of each β-sialon phosphor was measured as a relative value, with the luminance of the β-sialon phosphor of Comparative Example 1 being taken as 100%.

[0076] Absorption rate at 450 nm (%) For each β-sialon phosphor in the examples and comparative examples, a quantum efficiency measurement system (QE-2000, manufactured by Otsuka Electronics Co., Ltd.) was used to calculate the ratio of the excitation photon number at 450 nm of excitation light having an emission peak wavelength of 450 nm to the absorption photon number of each β-sialon phosphor at 450 nm, which was taken as the absorptance at 450 nm.

[0077] Luminous flux of the light-emitting device (%) Each β-sialon phosphor of the examples and comparative examples was used as the first phosphor. A phosphor of potassium fluorosilicate was used as the second phosphor. A phosphor 70, in which a first phosphor 71 and a second phosphor 72 were blended so that the target chromaticity coordinates in the chromaticity diagram of the CIE1931 color system were (x=0.262, y=0.223), was mixed with a silicone resin to obtain a resin composition. The content of the phosphor 70 in the resin composition is within a range of 20 parts by mass to 40 parts by mass with respect to 100 parts by mass of the silicone resin. For example, when the phosphor 70 is 100 parts by mass, the content of the β-sialon phosphor contained as the first phosphor is within a range of 20 parts by mass to 40 parts by mass, and the content of the second phosphor is within a range of 60 parts by mass to 80 parts by mass. The content of the β-sialon phosphor contained in the resin composition varies depending on the target color tone to be obtained and the size of the light-emitting device. Next, a molded body 40 having a recess was prepared, and a light emitting element 10 made of a gallium nitride compound semiconductor with an emission peak wavelength of 451 nm was placed on the bottom surface of the recess on a first lead 20, and then the electrodes of the light emitting element 10 were connected to the first lead 20 and the second lead 30 by wires 60. A resin composition was then injected into the recess of the molded body 40 using a syringe so as to cover the light emitting element 10, and the resin composition was cured to form a wavelength conversion member, thereby producing the light emitting device 1 shown in FIG. 1. The luminous flux of the light emitting device 100 containing each β-sialon phosphor of the examples and comparative examples was measured using an integral type total luminous flux measuring device. The luminous flux of the light emitting device using the β-sialon phosphor of Comparative Example 2 is taken as 100%, and the luminous flux of each light emitting device using each β-sialon phosphor of the examples is expressed as a relative value (%).

[0078] Amount of coating layer The Si contained in the entire β-sialon phosphor of each of the examples and comparative examples and the Si in the coating layer are measured by inductively coupled plasma optical emission spectrometry using an inductively coupled plasma optical emission spectrometer (Optima8300, manufactured by Perkin Elmer), and the amount of the coating layer relative to the total amount of the β-sialon phosphor is calculated from the amount of Si in the coating layer relative to the total amount of Si in the β-sialon phosphor. Even if the element contained in the coating layer is not silicon, the element contained in the coating layer and the element contained in the entire β-sialon phosphor can be measured using ICP-AES to calculate the amount of the coating layer relative to the total amount of the β-sialon phosphor.

[0079] BET specific surface area For each β-sialon phosphor of the examples and comparative examples, the BET specific surface area is measured by the one-point method using nitrogen gas as the adsorption gas by the BET method.

[0080] Coating layer thickness The β-sialon phosphor is embedded in resin, the resin is hardened, then the piece is cut to expose the cross section, the surface is polished with sandpaper, the surface is finished with a cross-section polisher (CP), and an SEM photograph is taken with a field emission scanning electron microscope (FE-SEM). The resin used to embed the β-sialon phosphor is epoxy resin so that the cross section of the β-sialon phosphor can be easily distinguished. FIG. 5 is an SEM photograph showing a cross section of a β-sialon phosphor according to Example 3. In order to easily confirm the coating layer, the cross section of the β-sialon phosphor in FIG. 5 is divided into three sections by enlarging the cross section by 10,000 times. FIG. 6A is an SEM photograph showing one of the three sections of the cross section of the β-sialon phosphor shown in FIG. 5, enlarged by 30,000 times. FIG. 6B is an SEM photograph showing one of the three sections of the cross section of the β-sialon phosphor shown in FIG. 5, enlarged by 30,000 times, like FIG. 6A, in which the inner line iL, the outer line oL, the first end line fL, the second end line sL, and the area A of the coating layer are written in order to explain the measurement of the thickness of the coating layer. As shown in Fig. 6B, the image of the cross section of one β-sialon phosphor is divided into three sections, and in the image of the cross section of the β-sialon phosphor in one section, the line indicating the inside of the coating layer 3 is the inner line iL, the line indicating the outside of the coating layer 3 is the outer line oL, the line connecting one end of the inner line iL to one end of the outer line oL is the first end line fL, and the line connecting the other end of the inner line iL to the other end of the outer line oL is the second end line sL. The thickness of the coating layer in one section is calculated from the area A of the coating layer surrounded by the inner line iL, the outer line oL, the first end line fL, and the second end line sL relative to the average value of the sum of the lengths of the inner line iL and the outer line oL by the following formula (1). The average value of the thickness of the coating layer in one section calculated in the sectioned cross section is divided by the number of sections into which the cross section of one β-sialon phosphor is divided, and this can be used as the thickness of the coating layer of one β-sialon phosphor. Thickness of coating layer = [Area of ​​coating layer at cross section ÷ (Length of outer line of coating layer + Length of inner line of coating layer) / 2] (1)

[0081] SEM images A scanning electron microscope (SEM) was used to obtain an SEM photograph of a secondary electron image of a β-sialon phosphor. FIG. 7A is an SEM photograph of a secondary electron image of a β-sialon phosphor according to Example 1 at a magnification of 5000 times, and FIG. 7B is an SEM photograph of a secondary electron image of a part of the surface of a β-sialon phosphor according to Example 1 at a magnification of 100000 times. FIG. 8A is an SEM photograph of a secondary electron image of a β-sialon phosphor according to Comparative Example 1 at a magnification of 5000 times, and FIG. 8B is an SEM photograph of a secondary electron image of a part of the surface of a β-sialon phosphor according to Comparative Example 1 at a magnification of 100000 times. FIG. 9A is an SEM photograph of a secondary electron image of a β-sialon phosphor according to Comparative Example 2 at a magnification of 5000 times, and FIG. 9B is an SEM photograph of a secondary electron image of a part of the surface of a β-sialon phosphor according to Comparative Example 2 at a magnification of 100000 times.

[0082] [Table 1]

[0083] In the β-sialon phosphors according to Examples 1 to 3, when the total of the phosphor particles and the coating layer measured by ICP-AES is taken as 100 mass%, the coating layer containing Si is in the range of 0.4 mass% to 5.0 mass%, and a film-like coating layer is disposed on the entire surface of the phosphor particle having the composition represented by formula (I). The β-sialons according to Examples 1 to 3 have an average particle diameter D measured by the FSSS method in the range of 9.0 μm to 10.0 μm, a BET specific surface area of ​​2.5 m, and a BET specific surface area of ​​2.5 m. 2 / g or more 20m 2 / g or less, has a large BET specific surface area relative to the average particle size, and has a film-like coating layer disposed on the entire surface of the phosphor particle. The β-sialon phosphors of Examples 1 to 3 have a film-like coating layer having a refractive index smaller than that of the phosphor particle disposed on the entire surface of the phosphor particle having the composition represented by formula (I), and therefore have a higher absorptance of light at 450 nm, which is the emission peak wavelength of excitation light, than the β-sialon phosphors of Comparative Examples 1 and 2, and emit light with a higher relative luminance than Comparative Example 1.

[0084] The β-sialon phosphors according to Examples 1 to 3 have a particle size ratio D / Dm of 0.6 or more, and are well dispersible. The β-sialon phosphors according to Examples 2 and 3 are redispersed in a liquid after a coating layer is disposed on the surface of the phosphor particles, so that aggregation of the β-sialon phosphor particles is reduced. Therefore, the β-sialon phosphors according to Examples 2 and 3 have a particle size ratio D / Dm larger than that of the β-sialon phosphor according to Example 1, and are better dispersible in the light-transmitting material. The light-emitting devices including the β-sialon phosphors according to Examples 1 to 3 have good dispersibility of the β-sialon phosphor in the light-transmitting material, and the light-emitting devices emit light with a high luminous flux because the light-emitting devices have efficient wavelength conversion and emit light with a high luminous flux due to the good dispersibility of the β-sialon phosphor in the light-transmitting material and the high absorptance of the excitation light of the β-sialon phosphor.

[0085] As shown in Figures 5, 6A and 6B, the β-sialon phosphor 1 according to Example 3 has a film-like coating layer 3 disposed over the entire surface of the phosphor particle 2. As shown in Figures 6A and 6B, in an SEM photograph showing one of three sections obtained by dividing the cross section of the β-sialon phosphor, the inner line iL of the coating layer 3, the outer line oL of the coating layer 3, a first end line fL connecting one end of the inner line iL to one end of the outer line oL, and a second end line sL connecting the other end of the inner line iL to the other end of the outer line oL can be drawn, and the thickness of the coating layer in one section can be derived from the above formula (1). The cross section of one β-sialon phosphor is divided into a plurality of sections, the thickness of the coating layer is derived for each section, and the total value of the thickness of the coating layer in each section is divided by the number of sections into which the cross section of one β-sialon phosphor is divided, whereby the thickness of the coating layer can be derived. The thickness of the coating layer of the β-sialon phosphor according to Example 3 is in the range of 50 nm to 200 nm, more specifically, in the range of 50 nm to 100 nm. The coating layer reduces light reflection and scattering, makes light more easily transmitted, and increases the light absorption rate of the phosphor particles, so that the β-sialon phosphor can emit light with high brightness. Since the amount (mass%) of the coating layer of the β-sialon phosphor according to Examples 1 to 3 is the same, the thickness of the coating layer of the β-sialon phosphor according to Example 3 was measured. Since the amount (mass%) of the coating layer of the β-sialon phosphor according to Examples 1 and 2 is the same as that of the β-sialon phosphor according to Example 3, it can be assumed that the thickness of the coating layer of the β-sialon phosphor according to Examples 1 and 2 is also approximately the same as that of the β-sialon phosphor according to Example 3.

[0086] 7A and 7B, the β-sialon phosphor of Example 1 has a smooth surface, and the entire surface of the phosphor particle is covered with a coating layer. Since the β-sialon phosphor of Example 1 has a larger BET specific surface area than Comparative Examples 1 and 2, it is presumed that the surface of the coating film, which is a dense silicon dioxide layer in the form of a film, has dense irregularities.

[0087] The β-sialon phosphors according to Comparative Examples 1 and 2 have an average particle size D measured by the FSSS method in the range of 9.0 μm to 10.0 μm, which is approximately the same as that of the β-sialon phosphors according to Examples 1 to 3, but have a BET specific surface area of ​​2.5 m 2 / g, resulting in a small BET specific surface area. The β-sialon phosphor of Comparative Example 1 had no coating layer, and therefore contained almost no silicon other than that contained in the phosphor particles as determined by ICP-AES. The β-sialon phosphor of Comparative Example 2 had colloidal silica arranged in granular form on the surfaces of the phosphor particles, and the amount of colloidal silica relative to the total amount of the phosphor particles and granular colloidal silica was as low as 0.19 mass%, and the BET specific surface area was also small at 2.5 m. 2 / g. In the β-sialon phosphors according to Comparative Examples 1 and 2, since there is no coating layer on the surface of the phosphor particles or the oxide present on the surface of the phosphor particles is granular, scattering of the excitation light incident on the β-sialon phosphor and reflection of the excitation light are not reduced, and the absorption of light having a wavelength of 450 nm is smaller than that of the β-sialon phosphors according to Examples 1 to 3, and the luminance is not high. The β-sialons according to Comparative Examples 1 and 2 have a particle size ratio D / Dm of 0.6 or more, specifically 0.8 or more, and have high dispersibility in the light-transmitting material. However, the relative luminous flux of the light-emitting device using the β-sialon phosphor according to Comparative Example 2 is not higher than the relative light of the light-emitting device using the β-sialon phosphors according to Examples 1 to 3.

[0088] As shown in FIGS. 8A and 8B, the β-sialon phosphor of Comparative Example 1 does not have a coating layer disposed thereon, and no significant irregularities are observed on the surfaces of the phosphor particles, which are β-sialon phosphors.

[0089] Although it is difficult to see in FIG. 9A, the β-sialon phosphor of Comparative Example 2 has granular oxide made of colloidal silica disposed on the surface of the phosphor particle as shown in FIG. 9B.

[0090] Embodiments according to the present disclosure include the following β-sialon phosphor and light emitting device.

[0091] [Item 1] Phosphor particles having a composition represented by the following formula (I); A β - sialon phosphor comprising a coating layer disposed on the surface of the phosphor particles and having a refractive index smaller than that of the phosphor particles, The β - sialon phosphor is measured by inductively coupled plasma emission spectrometry, and when the total of the phosphor particles and the coating layer is 100% by mass, the coating layer is 0.4% by mass or more. Si 6-z Al z O z N 8-z :Eu y (I) (In formula (I), y and z satisfy 0 < y ≤ 1.0 and 0 < z ≤ 4.2.) [Item 2] The β - sialon phosphor according to Item 1, wherein the coating layer is composed of an oxide, and the oxide contains at least one element selected from the group consisting of silicon, aluminum, zirconium, and yttrium. [Item 3] The average particle size D measured by the Fisher sub - sieve sizer method is in the range of 1 μm or more and 40 μm or less, and the BET specific surface area is 2.5 m 2 / g or more. The β - sialon phosphor according to Item 1 or 2. [Item 4] The β - sialon phosphor according to any one of Items 1 to 3, wherein the particle size ratio D / Dm of the average particle size D measured by the Fisher sub - sieve sizer method to the volume median diameter Dm measured by the laser diffraction particle size distribution measurement method is 0.6 or more. [Item 5] The cross-sectional image of one β-sialon phosphor is divided into two or more sections. In the cross-sectional image of one section of the β-sialon phosphor divided into two or more sections, the line indicating the inside of the coating layer is defined as the inner line, the line indicating the outside of the coating layer is defined as the outer line, the first end line that connects one end of the inner line and one end of the outer line, and the second end line that connects the other end of the inner line and the other end of the outer line. The thickness of the coating layer is derived from the area of the coating layer surrounded by the inner line, the outer line, the first end line, and the second end line with respect to the average value of the sum of the length of the inner line of the coating layer and the length of the outer line of the coating layer according to the following formula (1). The average value of the thickness of the coating layer obtained by dividing the total value of the thickness of the coating layer in each section derived in the divided cross-section by the number of sections into which the cross-section of one β-sialon is divided is within the range of 50 nm or more and 200 nm or less. The β-sialon phosphor according to any one of items 1 to 4. Thickness of coating layer = [Area of coating layer in cross-section ÷ (Length of outer line of coating layer + Length of inner line of coating layer) / 2] (1) [Item 6] The β-sialon phosphor according to any one of items 1 to 5, wherein the coating layer is disposed on the entire surface of the phosphor particles. [Item 7] A light-emitting device including a phosphor member including the β-sialon phosphor according to any one of items 1 to 6 and a light-transmitting material, and a light-emitting element having an emission peak wavelength in the range of 380 nm or more and 500 nm or less. [Item 8] The light-emitting device according to item 7, wherein the light-transmitting material has a refractive index smaller than that of the coating layer of the β-sialon phosphor. [Item 9] A method for manufacturing a β-sialon phosphor, including preparing phosphor particles having a composition represented by the following formula (I) and disposing a coating layer on the surface of the obtained phosphor particles. Si 6-z Al z O z N 8-z :Eu y (I) (In formula (I), y and z satisfy 0 < y ≤ 1.0 and 0 < z ≤ 4.2.) [Item 10] Item 10. A method for producing a β-sialon phosphor according to item 9, comprising redispersing the obtained β-sialon phosphor in a liquid. [Industrial Applicability]

[0092] The β-sialon phosphor of the present disclosure can be used as a phosphor contained in a wavelength conversion member of a light emitting device, and a light emitting device containing the β-sialon phosphor can be suitably used as an illumination light source, an LED display, a backlight light source for liquid crystal displays, a traffic signal, an illuminated switch, various sensors, various indicators, etc. [Explanation of symbols]

[0093] 1: β-sialon phosphor, 2: phosphor particle, 3: coating layer, 10: light-emitting element, 20, 30: lead electrode, 40: molded body, 50: wavelength conversion member, 60: conductive wire, 70: phosphor, 71: first phosphor, 72: second phosphor, 100: light-emitting device.

Claims

1. Phosphor particles having a composition represented by the following formula (I); A coating layer disposed on a surface of the phosphor particle and having a refractive index smaller than that of the phosphor particle, A β-sialon phosphor, wherein the β-sialon phosphor is measured by inductively coupled plasma optical emission spectroscopy, and the coating layer accounts for 0.4 mass% or more when the total of the phosphor particles and the coating layer is taken as 100 mass%. Yes 6-z Al z O z N 8-z :Eu y (I) (In formula (I), y and z satisfy 0<y≦1.0 and 0<z≦4.2.)

2. 2. The β-sialon phosphor according to claim 1, wherein the coating layer is made of an oxide, and the oxide contains at least one element selected from the group consisting of silicon, aluminum, zirconium, and yttrium.

3. The average particle size D measured by the Fisher subsieve sizer method is in the range of 1 μm to 40 μm, and the BET specific surface area is 2.5 m 2 The β-sialon phosphor according to claim 1 or 2, wherein the β-sialon phosphor has a molecular weight of 1.0 / g or more.

4. 3. The β-sialon phosphor according to claim 1, wherein a particle size ratio D / Dm of an average particle size D measured by a Fisher subsieve sizer method to a volume median diameter Dm measured by a laser diffraction particle size distribution measurement method is 0.6 or more.

5. A cross-sectional image of one β-sialon phosphor is divided into two or more sections, and in the cross-sectional image of the β-sialon phosphor of one of the two or more sections, a line indicating the inside of the coating layer is defined as an inner line, a line indicating the outside of the coating layer is defined as an outer line, a first end line connecting one end of the inner line to one end of the outer line, and a second end line connecting the other end of the inner line to the other end of the outer line, and a thickness of the coating layer is calculated from an area of ​​the coating layer surrounded by the inner line, the outer line, the first end line, and the second end line relative to an average value of the sum of the length of the inner line of the coating layer and the length of the outer line of the coating layer, using the following formula (1):

3. The β-sialon phosphor according to claim 1 or 2, wherein an average thickness of the coating layer obtained by dividing the total value of the thickness of the coating layer in each section derived in the sectioned cross section by the number of sections into which a cross section of one β-sialon is sectioned is within the range of 50 nm or more and 200 nm or less. Thickness of coating layer = [area of ​​coating layer in cross section ÷ (length of outer line of coating layer + length of inner line of coating layer) / 2] (1)

6. The β-sialon phosphor according to claim 1 , wherein the coating layer is disposed on the entire surface of the phosphor particle.

7. 3. A light emitting device comprising: a fluorescent member containing the β-sialon phosphor according to claim 1 or 2 and a translucent material; and a light emitting element having an emission peak wavelength in the range of 380 nm to 500 nm.

8. The light emitting device according to claim 7 , wherein the light transmissive material has a refractive index smaller than that of the coating layer of the β-sialon phosphor.

Citation Information

Patent Citations

  • JP173868A

  • Method for producing phosphor, phosphor and lighting equipment

    JP2007326981A